Construction of a matchstick-shaped Au@ZnO@SiO2–ICG Janus nanomotor for light-triggered synergistic antibacterial therapy. (19th August 2022) - Liu, Xuan; Liu, Huaxiao; Zhang, Jinzha; Hao, Yijie; Yang, Hongna; Zhao, Wenbo; Mao, Chun
Abstract : Nanomotors can provide support for increasing the action radius of ROS and improving the membrane insertion ability of a photosensitizer. Abstract : The drug-resistance of bacteria poses a serious threat to public health, so the exploration of new antibacterial materials has attracted extensive attention. Here, we report Au@ZnO@SiO2 –ICG nanomotors as an antibacterial candidate. Firstly, we prepared the Janus structure Au@ZnO loaded with indocyanine green (ICG) and constructed a synergistic antibacterial platform with photothermal and photodynamic properties triggered by dual light sources. Specifically, the metal/semiconductor heterostructure of Au@ZnO has a synergistic effect under ultraviolet (UV) irradiation, which can adjust the transfer of interface electrons, so as to greatly improve the generation of cytotoxic ROS for photodynamic sterilization. The loaded ICG is an effective photosensitizer, and can induce a stronger photothermal effect in collaboration with Au under near-infrared light (NIR). In addition, the asymmetric structures of nanomotors have autonomous movement with the help of generated temperature gradient when exposed to NIR light, conducive to breaking through the bacterial membrane and improving the membrane insertion ability of antibacterial therapeutic agents. The results indicate that the prepared Au@ZnO@SiO2 –ICG nanomotors show excellent light responses and synergistic sterilization ability to Gram-negative Escherichia coli ( E. coli ) and Gram-positive Staphylococcus aureus ( S. aureus ). This study will provide a new idea for the application of metal–semiconductor nanocomposites in the treatment of bacterial infection.